The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.4049/jimmunol.170.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low-Avidity CD4+ T Cells Using Recombinant Artificial APC: Following the Antiovalbumin Immune Response

Abstract: Subtle differences oppose CD4+ to CD8+ T cell physiologies that lead to different arrays of effector functions. Interestingly, this dichotomy has also unexpected practical consequences such as the inefficacy of many MHC class II tetramers in detecting specific CD4+ T cells. As a mean to study the CD4+ anti-OVA response in H-2d and H-2b genetic backgrounds, we developed I-Ad- and I-Ab-OVA recombinant MHC monomers and tetramers. We were able to show that in this particular system, despite normal biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…Such aAPC were very efficient in identifying class II-restricted Ag-specific T cells but their capacity to effectively stimulate T cells was limited to some highaffinity T cell hybridomas which do not require costimulation. As also suggested by elegant work from others (18), using similar technology, suboptimal stimulatory capacity was presumably due to the combination of several factors, including inappropriate orientation of MHC molecules, lack of organization, and insufficient local concentration of T cell ligands in the area of contact between the aAPC and T cell. Taken together, these data show that the efficiency of these artificial systems in inducing T cell activation may be influenced by the relative density of MHC-peptide complexes available at the point of interaction.…”
mentioning
confidence: 83%
“…Such aAPC were very efficient in identifying class II-restricted Ag-specific T cells but their capacity to effectively stimulate T cells was limited to some highaffinity T cell hybridomas which do not require costimulation. As also suggested by elegant work from others (18), using similar technology, suboptimal stimulatory capacity was presumably due to the combination of several factors, including inappropriate orientation of MHC molecules, lack of organization, and insufficient local concentration of T cell ligands in the area of contact between the aAPC and T cell. Taken together, these data show that the efficiency of these artificial systems in inducing T cell activation may be influenced by the relative density of MHC-peptide complexes available at the point of interaction.…”
mentioning
confidence: 83%
“…However, both flTCR-and scTCR-transduced primary T cells were stained poorly with the dimer (data not shown). In the future, we plan to try an improved tetramer technology 36 to identify the differential affinity between flTCR and scTCR. Holler et al 37 demonstrated that the low affinity of scTCR molecules could be dramatically increased by an in vitro selection system through site-directed mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…2B, in general, 90% of the p31-I-A g7 -expanded T reg population failed to stain for the p31-I-A g7 multimer when analyzed by flow cytometry. It was possible that the unstained population was comprised of p31-I-A g7 -reactive cells with TCRs with too low of an affinity to be detected by flow cytometry (14). Alternatively, this population could be comprised of cells that were expanding in an Ag-nonspecific manner.…”
Section: Rare Ag-specific T Reg Can Be Expanded From Wild-type Nod Micementioning
confidence: 99%
“…The 1040-31 peptide, specific for BDC2.5 TCR Tg ϩ T cells, consisted of amino acids YVRPLWVRME (9). The HEL [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] protein consisted of amino acids AMKRHGLDNYRGYSL. GAD 286 -300 was a gift from E. Sercarz (Torrey Pines Institute for Molecular Studies, San Diego, CA).…”
Section: Reagentsmentioning
confidence: 99%